Pelatihan Ms Office Dalam Peningkatan Keterampilan Guru SD dan SMP - Naria Fitriani; Ardian Ardian; Dewi Maya Sari; Mislinawati Mislinawati; Cut Yunina Eriva; Muhammad Abthahi; Hilmi Hilmi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Every teacher is required to make interesting learning materials quickly and precisely. With current technological developments, these materials are no longer written manually. The use of Ms. Office has been widely used because it is faster in completing teaching materials, exam questions and so on. Based on the initial interview, the Headmaster said that the majority of the school’s teachers were not proficient in applying Ms. Office in making materials needed during the teaching and learning process. To provide a solution, this community service activity was carried out in the form of training for Ms. Office for 30 elementary and junior high school teachers. With a total implementation time of two days (16 hours) which includes theory and practice, the results show that there is an increase in ability to operate Ms. Office in the form of Ms. Word, Excel and PowerPoint so that teachers can not only produce the necessary materials but also complete other school administration more quickly.